The Effect of Sharia Supervisory Board Characteristics on Islamic Social Reporting Disclosures of Islamic Banking in Indonesia - Rukmana, Chindy Aidil Fitri; Indriani, Dede Vina; Ramadhina, Elvina Zahrah; Rybca, Shalwa Ainun; Mayasari, Ine; Setiawan, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study examines the role of the characteristics of the Sharia Supervisory Board (SSB) in increasing the disclosure of social responsibility of sharia banking in Indonesia using the Islamic Social Reporting (ISR) index for the 2017-2022 period. SSB characteristics tested in this study were size, number of meetings, multiple positions, expertise, age, and the presence of women. This study uses a quantitative method, a descriptive approach, with the sample being the entire population of this research, namely all Indonesian sharia commercial banks registered with the OJK during the 2017-2022 period, totaling 16. This research was then tested using panel data regression. The estimation results of the Random Effect model in this study indicate that SSB expertise and age have a positive effect on ISR disclosure. However, SSB size was found to have a negative influence on ISR disclosure. This research contributes to the development of Islamic corporate governance literature on ISR disclosure and provides insights and guidelines for Islamic banking in Indonesia and DSN-MUI regarding the decision-making of appropriate SSB characteristics in its placement in Islamic banking in Indonesia.